Rapid visual detection of Escherichia coli and Vibrio cholerae Heat-labile enterotoxins by nitrocellulose enzyme-linked immunosorbent assay. - Beutin, L (1984)
A modification of the enzyme-linked immunosorbent assay for a sensitive and rapid visual detection of heat-labile enterotoxins from Escherichia coli and Vibrio cholerae is described. Small amounts of bacterial supernatant fluids are bound to nitrocellulose filters which are used as sorbents in the nitrocellulose enzyme-linked immunosorbent assay. The test is based on the immunological similarity between V. cholerae and E. coli heat-labile enterotoxins. Six isolates of V. cholerae and 48 isolates of E. coli were examined for heat-labile enterotoxins by the nitrocellulose enzyme-linked immunosorbent assay and the Vero cell bioassay. With some strains, the nitrocellulose enzyme-linked immunosorbent assay was found to be more sensitive for detection of E. coli heat-labile enterotoxin than the Vero cell test. A similar result was obtained by endpoint titration of heat-labile enterotoxin-positive E. coli H10407 culture fluid in both assays. The sensitivity of the nitrocellulose enzyme-linked immunosorbent assay for the detection of purified cholera toxin was at a total level of 1 ng, which is a good result when compared with other serological assays.